PERTANGGUNG JAWABAN PIDANA TERHADAP TERPUBLIKASINYA DATA REKAM MEDIS PASIEN - Hardi Done; Agnes Fitria Ananda Kolo (Jurnal Ilmu Hukum Kanturuna Wolio, 2026)
This research aims to examine the criminal responsibility arising from the publication of patient medical records data using a normative juridical approach. In the legal context, patient medical records data is highly sensitive information protected by various laws and regulations. This study aims to analyze the legal framework governing the protection of medical data, as well as the legal consequences that may be imposed on parties involved in the unauthorized dissemination of such data. The research method employed is a normative juridical approach, focusing on the analysis of relevant laws and regulations, including Law No. 36 of 2009 on Health, Law No. 11 of 2008 on Electronic Information and Transactions, and the Personal Data Protection Law. This study also includes an analysis of legal doctrines and jurisprudence related to violations of privacy and the confidentiality of medical data. The findings indicate that violations of the legal provisions governing the protection of medical data can result in criminal sanctions, both for individuals and institutions responsible. Additionally, the research identifies various factors contributing to these violations, such as a lack of understanding regarding the importance of data confidentiality and weak oversight of medical data management practices. This thesis also provides recommendations for enhancing the protection of medical data, including the need for regulatory strengthening, increasing legal awareness among medical personnel, and developing more effective oversight mechanisms. Thus, this research is expected to make a significant contribution to the understanding of the importance of medical data protection and the legal implications for violators, as well as to encourage better protection efforts for patients' personal data.